Int. J. Adv. Res. Biol. Sci. 2017
DOI: 10.22192/ijarbs.2017.04.12.024
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Experimental Studies on the Spleen of Young and Aged Balb/C and Cd-1 Mice

Abstract: Immunosenescence is generally related to weaker immune responses since, elderly individuals do not respond to immune challenge as strongly as the youngs. Spleen is the largest secondary lymphoid organ present almost in all vertebrates. In addition of its skill as a main part of immune system, it serves also as a graveyard for old damaged red blood cells, storage of blood as well as production of antibodies and keeping bodily fluids in balance. So, the present study aims to elucidate its complex histological or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Studies suggest many variances between different animal species and even within the same specie's strain individuals around life span. 39 Earlier reports indicated that Balb/c immunized with cruzipain-induced heart autoimmunity, whereas C57bl/6 mice were resistant. Therefore, during the immune response, different genetic background affects several parameters like B cell activation.…”
Section: Discussionmentioning
confidence: 99%
“…Studies suggest many variances between different animal species and even within the same specie's strain individuals around life span. 39 Earlier reports indicated that Balb/c immunized with cruzipain-induced heart autoimmunity, whereas C57bl/6 mice were resistant. Therefore, during the immune response, different genetic background affects several parameters like B cell activation.…”
Section: Discussionmentioning
confidence: 99%
“…It has many functions, such as haematopoiesis, controlling the amount of blood cells, creating regular immune responses, and blood filtration and storage. T and B lymphocytes, which are immunocompetent cells, settle in the spleen (1,2,48). This organ varies in its characteristics by species, genetics, and age, being ellipsoid, triangular, and globular in the ostrich, duck, and chicken, respectively (8,48).…”
Section: Discussionmentioning
confidence: 99%
“…Histologically, splenic parenchyma is observed in two different areas as white and red pulp. While white pulp contains periarteriolar deposition of dense and well-organised lymphocytes, red pulp has sinusoidal cavities, blood vessels, splenic cords, and reticular cells ( 2 ). Sur and Çelik ( 49 ) observed that white pulp development started on the 13 th day of incubation.…”
Section: Discussionmentioning
confidence: 99%